FREQUENCY OF SPLENOMEGALY IN DENGUE FEVER IN CHILDREN - Arshad, Kashan; Sheikh, Saifullah; Naqvi, Syeda Umm-ul-Baneen; Sarwar, Imran; Javaid, Sulman; Asghar, Madiha; Butt, Muhammad Asghar (Journal of Ayub Medical College Abbottabad, 2015)
Background: Dengue Fever is caused by arthropod born viruses.According to World Health Organization approximately 50-100 million infections of dengue fever occur yearly. Objective of this study was to determine the frequency of splenomegaly in dengue fever in children. Methods: This cross sectional study was conducted at the Department of Paediatrics, Allied Hospital, Faisalabad, during a period from June 2012 to May 2013 by including 93 Children, aged 4-14 years presenting with fever of less than 14 days with thrombocytopenia and positive IgM or IgM and IgG dengue antibodies by ELISA. Patients were thoroughly evaluated by detailed history and clinical examination. Ultrasonography of the patients was performed to confirm the splenomegaly. The data was analysed to determine the frequency and percentage of disease. Results: Out of 93 children, 51 (54.8%) were male and 42 (45.2%) were female. The most common clinical presentation was noted is chills and rigors in 80 (86.02%). Unusual clinical features were encephalopathy in 37 (39.78%) followed by bleeding manifestations and upper respiratory tract infection (upper RTI). Splenomegaly was seen in 45 (48.4%) children. Conclusion: Dengue fever is increasingly presenting with atypical presentation like splenomegaly, encephalopathy, bleeding manifestations and upper RTI. Keywords: Dengue fever, Splenomegaly, Atypical presentation